Inibidor de nitrificação e manejos do dejeto líquido de suínos em solo cultivado com milho e trigo - Pinto, Marlo Adriano Bison (2016)
The pig farming as a key member of the agricultural sector depends on strategies to improve the use of N from pig slurry by crops, mitigating the negative environmental impact caused by its misuse. Among the strategies under study in other countries to mitigate possible impacts include the injection of liquid manure in the soil and the use of nitrification inhibitors. In Brazil, research in this area is still in its infancy. The aim of this study was to evaluate the effect of the injection of liquid waste pigs in the soil and the addition of nitrification inhibitor on the mineral nitrogen from the soil and productivity of crops succession wheat/corn under no-tillage system. The survey was conducted from July 2014 to April 2015 on a Red Latosol at the Federal University of Santa Maria campus Frederick and the treatments were: T1 - application in surface DLS (SUP), T2 - injection in the subsurface of the DLS (INJ), T3 - surface application of DLS + addition of dicyandiamide (SUP + DCD), T4 - injection in the subsurface of the DLS + addition of dicyandiamide (INJ + DCD), T5 - without application of manure witness and dicyandiamide (Test.) and T6 - NPK application in mineral form (NPK). The product "Argotic Plus", which contains in its formulation 81.4% of the nitrification inhibitor dicyandiamide (DCD), was mixed with the waste at a dose of 10 kg ha-1. The nitrification inhibitor (DCD) preserved the N of the manure applied to the soil in the form of ammonia, thus, the application of manure increased the productivity of wheat and maize, with results similar to urea. The application of DCD delayed nitrification of ammonia nitrogen from manure in the soil at least 33 DAA when surface and subsurface to 38 DAA, for the wheat crop. For the treatments with injection of pig slurry, the use of the inhibitor maintained increased amount of ammonia in the soil compared to the absence of inhibitor until the first 46 DAA in maize. The results of this work show that the injection of liquid swine manure with DCD has higher residual effect to the other treatments in corn , and the nitrification inhibitor should only be used in order to improve the plant parameters and productivity if the manure it is injected into the soil.